Multi-track Cabinet based on Metamorphic Mechanism - Yu Haoliang; Zheng Weilong; Zhu Jianfeng (Jixie chuandong)
With the principle of metamorphic mechanism,aiming at the right- angle space problem often encountered in the cabinet arrangement,a new kind of cabinet is designed and the design plan and size calculation are given.